Konsep Putusan Pemaaf Oleh Hakim (Rechterlijk Pardon) Sebagai Jenis Putusan Baru Dalam KUHAP - Alfret; Mardian Putra Frans (Fakultas Hukum Universitas Bhayangkara Jakarta Raya, 2023)
Of the various articles that have undergone changes and additions in the new Criminal Code, one of them is interesting, namely Article 54 related to forgiveness by judges. However, whether the concept of forgiveness decision by the judge in the new Criminal Code has a position as a decision in the Criminal Procedure Code or the Criminal Procedure Bill. This research uses a normative juridical research method, which examines the problem by referring to positive law. The results of this study indicate the need for additional types of forgiveness decisions in the Criminal Procedure Bill as a form of criminal law reform because the provisions related to the types of decisions in the Criminal Procedure Code and the Criminal Procedure Bill are currently unable to accommodate forgiving decisions by judges. By examining in more depth the concept of forgiveness by the judge, it will appear that neither the Criminal Procedure Code nor the Criminal Procedure Bill contains the type of forgiveness decision.